Flat-band enhanced antiferromagnetic fluctuations and superconductivity in pressurized CsCr3Sb5 - Siqi Wu; Chenchao Xu; Xiaoqun Wang; Hai-Qing Lin; Chao Cao; Guang-Han Cao (Nature Communications)
Abstract The spin dynamics and electronic orders of the kagome system at different filling levels stand as an intriguing subject in condensed matter physics. By first-principles calculations and random phase approximation analyses, we investigate the spin fluctuations and superconducting instabilities in kagome phase of CsCr3Sb5 under high pressure. At the filling level slightly below the kagome flat bands, our calculations reveal strong antiferromagnetic spin fluctuations in CsCr3Sb5, together with a leading s ±-wave and a competing (d x y , $${d}_{{x}^{2}-{y}^{2}}$$ d x 2 − y 2 )-wave superconducting order. Unlike the general intuition that the flat bands are closely related to the ferromagnetic correlations, here we propose a sublattice-momentum-coupling-driven mechanism for the antiferromagnetic fluctuations enhanced from the unoccupied flat bands. The mechanism is generally applicable to kagome systems where the Fermi level intersects near the flat bands, offering a new perspective for future studies of geometrically frustrated systems.